2013
DOI: 10.1111/1365-2745.12172
|View full text |Cite
|
Sign up to set email alerts
|

Invasive plants escape from suppressive soil biota at regional scales

Abstract: Summary 1.A prominent hypothesis for plant invasions is escape from the inhibitory effects of soil biota. Although the strength of these inhibitory effects, measured as soil feedbacks, has been assessed between natives and exotics in non-native ranges, few studies have compared the strength of plantsoil feedbacks for exotic species in soils from non-native versus native ranges. 2. We examined whether 6 perennial European forb species that are widespread invaders in North American grasslands (Centaurea stoebe, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 59 publications
4
101
6
Order By: Relevance
“…Several studies ( Callaway et al, 2004 ;Maron et al, 2014 ) have found different plant-soil feedback processes between C. stoebe and soil biota at home compared with its introduced North American range, suggesting that in the introduced range C. stoebe escapes at least partially from soil pathogens. However, we found good establishment of C. stoebe in the empty subplots, indicating that the presence of natural enemies, different soil pathogens, postintroduction evolution or seed quality are not the main factors contributing to the failure of establishment of C. stoebe in the mixed species assemblages at home, unless these factors differ fundamentally between the empty subplots and those with experimental plant assemblages.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies ( Callaway et al, 2004 ;Maron et al, 2014 ) have found different plant-soil feedback processes between C. stoebe and soil biota at home compared with its introduced North American range, suggesting that in the introduced range C. stoebe escapes at least partially from soil pathogens. However, we found good establishment of C. stoebe in the empty subplots, indicating that the presence of natural enemies, different soil pathogens, postintroduction evolution or seed quality are not the main factors contributing to the failure of establishment of C. stoebe in the mixed species assemblages at home, unless these factors differ fundamentally between the empty subplots and those with experimental plant assemblages.…”
Section: Resultsmentioning
confidence: 99%
“…The presence or absence of certain soil biota can also explain why some exotic plant species are able to occur at higher abundance in the non-native versus native range. Maron et al, (2014) found that soils from the native range of some invasive plant species had a strong suppressive potential on these plants, whereas this is not the case in soils in the nonnative range. This suggests that different composition of soil community can strongly alter the structure of vegetation.…”
Section: Introductionmentioning
confidence: 91%
“…bolstered by broad comparative studies showing that invasives support fewer pathogens than do natives (Mitchell and Power 2003;Mitchell et al 2010), as well as indications that some invasives suffer from strong negative soil feedbacks where they are native (Reinhart et al 2003;Zuppinger-Dingle et al 2011;Yang et al 2013;Maron et al 2014). It is further supported by research suggesting that invasives gain a competitive edge over natives as a result of this inequality in the strength of soil feedbacks (Reinhart and Callaway 2006;Petermann et al 2008).…”
Section: Introductionmentioning
confidence: 94%